(3cJGH aj GdMSGHs
(3ChdgG (B:s
(3bGd Gdehdi GdeDda QMeg Gddg CeG HYO MeO Gddg YOO fYeGFg hGdTcQ dg Ydi JhGdi BdGFg hGdUdGI hGdSdGe Ydi eMeO NjQ CfHjGFg hYdi Bdg hCUMGHg NjQ ChdjGFg aEf cJGHi GdehVhY ai UfGYI GdghGA GdeSei HGdeYhfI deG cHQYdi gee Cgd GdYUQ s
(3BNQgG (B:s
(3dCf ZGdH eSGFdg dG jNQL Yf GdCYOGO hcPdc cd eSFdI JQLY Edi GdCYOGO GdeJfGSHI ef ZjQ EMJjGL Edi eG PcQg GdeJbOehf ef JfRjd GdeSGFd ai gPg GdBdg hCSFd Gddg GdYXje GdhgGH Cf jhabfG ddYed hjYUefG Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdQjGVjGJs